基于磁学定量检测氧化型低密度脂蛋白的方法及系统 (2025)
本申请公开了一种基于磁学定量检测氧化型低密度脂蛋白的方法及系统，所述方法包括：制备磁性免疫探针，并采用磁学信号激发能量转化为电信号进行偶联效率的计算；构建包含检测区、质控区和结合区的免疫层析试纸条，并结合标准曲线的建立实现氧化型低密度脂蛋白浓度的检测；将待测样本施加于试纸条样品垫，通过与结合垫位置与已标记氧化型低密度脂蛋白抗体的磁性微粒相结合，通过在硝酸纤维素膜上流动至标记另一株抗体的部位，通过抗原抗体的结合作用，经特异性识别形成磁颗粒富集区域，通过磁学信号采集及数据处理，以对氧化低密度脂蛋白进行定量检测。通过本申请的方案，能够实现对Ox-LDL的高灵敏度、高特异性以及快速检测。 The invention discloses a method and system for quantitatively detecting oxidized low-density lipoprotein based on magnetis.The method comprises the steps that a magnetic immune probe is prepared, and coupling efficiency is calculated by converting magnetic signal excitation energy into an electric signal; an immunochromatography test strip comprising a detection area, a quality control area and a binding area is constructed, and the detection of the concentration of the oxidized low-density lipoprotein is realized in combination with the establishment of a standard curve; a to-be-detected sample is applied to the sample pad of the test strip, the to-be-detected sample is combined with the magnetic particles marked with